Global Economic Prospects : Commodity Markets Outlook, April 2014 - Baffes, John; Cosic, Damir (World Bank, Washington, DC, 2014)
The key commodity price indices were broadly stable during 2014. Energy prices changed little, only 0.4 higher than 2013; agricultural prices increased 1.8 percent on weather-related concerns and metal prices declined 3.2 percent on Chinese demand weakness. Agricultural prices are projected to ease in 2014 under the assumption that current crop conditions will persist for the next crop year. A weather-induced increase in maize and wheat prices in late February and March 2014 was partly offset by declines in rice prices. The report includes detailed market analysis for most primary commodities, including energy, metals, agriculture, precious metals, and fertilizers. It also includes historical and recent price data as well as price forecasts going up to 2025.